Pengelolaan pendidikan agama Islam di Islamic full day school Salman al-Farisi Bandung - Sumarna, Andri Ramdani; Asyafah, Abas; Kosasih, Aceng (Universitas Pendidikan Indonesia, 2017)
The purpose of this study is to know the management of Islamic religious education in full day school Islamic Junior High School Salman Al-Farisi Bandung starting from planning, implementation, and results and advantages and weaknesses of PAI in full-day school program. The research conducted using qualitative approach descriptive method. To obtain research data, researchers used the method of observation, interview, and documentation. The results showed that: (1) Planning of Islamic education expanded into subjects tilÄwati, taá¸¥fiÅ¼, matrikulasi, and hours wali kelas for the seven sunnah habituation. Basic competencies are mapped into aspects of leadership and green education. (2) The implementation of Islamic education is carried out by teachers of PAI, other teacher and special teachers integrated in leadership, green education and IMTAQ (3) The result of Islamic education is evidenced by the special report of the application of Islamic education (4) with educational background become weakness of SAF Islamic Junior High School full day. The integration of the concept of leadership, green education in PAI as well as the habituation of seven sunnah became the excellence of SMP SAF Islamic full day school to achieve khalÄ«fatullÄh fÄ« al-Ará¸i the rahmatan lil'ÄlamÄ«n